Answer:
see explanation
Step-by-step explanation:
To factorise the quadratic consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x term.
product = 2 × - 6 = - 12 and sum = + 11
The factors are + 12 and - 1
Use these factors to split the middle term
2x² + 12x - x - 6 = 0 ( factor the first/second and third/fourth terms )
2x(x + 6) - 1(x + 6) = 0 (factor out (x + 6) )
(x + 6)(2x - 1) = 0
equate each factor to zero and solve for x
x + 6 = 0 ⇒ x = - 6
2x - 1 = 0 ⇒ x = [tex]\frac{1}{2}[/tex]